River Water Pollution Control Strategy Due to Coal Mining Activities (Case Study in Kungkilan River West Merapi District, Lahat) - Eddy Suroso; Muhammad Said; Satria Jaya Priatna (Sriwijaya Journal of Environment, 2017)
Abstract: Kungkilan River is under the administration of West Merapi Sub-district, Lahat, which is potential to degrade its water quality, resulted from the activity of coal mining. This research is aimed to analyze the quality of water in Kungkilan River in every segment of coal mining campany and proposing a recommendation of management strategy of river pollution. This research applied the descriptive analysis with the quantitative approach using sample survey method. The analysis of the recommendation of management strategy of river pollution was conducted through SWOT method. The sample of water in Kungkilan River was collected from 5 station. The sample of waste water was collected from 7 spots of Sludge Sedimentation Pond of the coal mining campany. It was collected during the dry and rainy season. It can be concluded that the quality of water in Kungkilan River has been degrading right after streaming through the area of coal mining. In the dry season, each segment meets the calculation of the capacity of water pollution for TSS parameter, while in the rainy season, segment IV exceeds the capacity. In the rainy season, the quality of water in Kungkilan River in the station S-02, S-03 and S-04 encounters a self-purification process, while in Station S-05 is in the condition of moderate pollution. Based on hose finding, it is recommended that the management strategy of Kungkilan River pollution can be conducted through having research on the determination of water classification and the capacity of water pollution in Kungkilan River and supervising the quality of water periodically and continually; improving the frequency of supervision by PPLH/PPLHD personnel and functionally; moving the water disposal canal to other spots and conducting vegetation; regulating law administratively, both civil and criminal law, to the companies violating the regulation of water pollution management; and benefitting the CSR program of the company.Keywords: Kungkilan River, the quality of river, management strategy.Abstrak (Indonesian): Sungai Kungkilan berada di wilayah administrasi Kecamatan Merapi Barat, Kabupaten Lahat yang berpotasi terjadi penurunan kualitas air akibat kegiatan pertambangan batubara. Penelitian ini bertujuan menganalisis kualitas air Sungai Kungkilan di setiap segmen perusahaan pertambangan batubara, serta memberikan rekomendasi strategi pengendalian pencemaran air sungai. Penelitian ini memakai analisis deskriptif dengan pendekatan kuantitatif dengan sample survey method, dan analisis rekomendasi strategi pengendalian pencemaran air dengan metode SWOT. Pengambilan sampel air Sungai Kungkilan dilakukan di 5 stasiun, dan sampel air limbah dan/atau air limpasan dari di outlet Kolam Pengendap Lumpur (KPL) lokasi perusahaan pertambangan batubara berjumlah 8 dan 7 titik. Pengambilan sampel air limbah dan atau air limpasan, dan air Sungai Kungkilan dilakukan pada musim kemarau dan musim hujan. Dapat disimpulkan bahwa kualitas air Sungai Kungkilan telah terjadi penuruan setelah melintasi kegiatan pertambangan batubara, Perhitungan daya tampung beban pencemaran air untuk parameter TSS, pada musim kemarau di setiap segmen masih memenuhi daya tampung, namun pada musim penghujan di segmen IV telah melebihi daya tampung. Status mutu air Sungai Kungkilan di stasiun S-02, S-03, dan S-04 pada musim penghujan terjadi proses self purification, sedangkan di stasiun S-05 tetap dalam kondisi cemar sedang. Rekomendasi strategi pengendalian pencemaran air Sungai Kungkilan, yaitu: melakukan kajian penetapan kelas air dan daya tampung beban pencemaran air Sungai Kungkilan, serta pemantauan kualitas air secara periode dan kontinu; peningkatan frekuensi kegiatan pengawasan oleh personil PPLH dan/atau PPLHD dan berstatus fungsional; pemindahan saluran pembuangan air limbah ke badan air lainnya dan pelaksanaan revegetasi; penerapan sanksi penegakan hukum baik secara administratif, perdata dan/atau pidana bagi perusahaan pelanggar peraturan pengendalian pencemaran air; dan pemanfaatan program CSR perusahaan. Katakunci: Sungai Kungkilan, kualitas air sungai, strategi pengendalian.